PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN LABORATORIUM LABBIOGEN DI SURABAYA - Jois Fera Diana; Achmad Djoni Sudirman (Universitas Dharmawangsa, 2023)
This study aims to determine whether service quality and company image have an effect on customer satisfaction at the Labbiogen Laboratory in Surabaya. This research is a descriptive quantitative type with a population of 92 customers of Labbiogen Laboratory in the city of Surabaya and samples were obtained using a purposive sampling technique, where the criterion was that the customer had at least checked at least 2 times. The research data is primary data using a questionnaire which is distributed using a Google Form, which is done to avoid transmission of the Covid-19 virus. The results showed that: Service Quality and Corporate Image have a significant effect on Customer Satisfaction of the Labbiogen Laboratory in Surabaya, both partially and simultaneously. From the results of the coefficient of determination, the R2 value is 0.479 or 47.90%. This shows that customer satisfaction can be explained by 47.90% by the independent variables namely Service Quality and Company Image). While 52.10% of the variable Customer Satisfaction is explained by other variables outside the independent variables in this study.